Early unrestricted vs. partial weight bearing after uncemented total hip arthroplasty: a systematic review and meta-analysis - Huang, Li; Han, Weiyu; Qi, Weizhong; Zhang, Xiaomeng; Lv, Zhou; Lu, Yao; Zou, Danfeng (Frontiers in Surgery, 2023)
Background: The choice of postoperative weight bearing protocol after uncemented total hip arthroplasty (THA) remains controversial. The aim of this study was to assess the efficacy and safety of immediate unrestricted weight bearing (UWB) compared with partial weight bearing (PWB) in patients undergoing uncemented THA. Methods: Relevant articles were retrieved from electronic databases. Both randomized controlled trials (RCTs) and non-RCTs were included but analyzed separately. All functional and clinical outcomes with at least 2 independent study outcomes were meta-analyzed. Results: A total of 17 studies were investigated. No adverse effect was found regarding micromotion of the femoral stem with immediate UWB following uncemented THA. There was also no correlation between immediate UWB and failure of ingrowth fixation and higher risks of femoral stem subsidence and surgical revision in RCTs. Harris hip score was better in patients with immediate UWB than those with PWB at 1 year post surgery, but the difference was not statistically significant. Conclusions: Immediate UWB did not have extra harm compared with PWB in patients undergoing uncemented THA. UWB was not superior to PWB. Considering the improvement of Harris score and the compliance of patients, UWB can be encouraged in THA rehabilitation.